OPTIMIZING SHIPPING COSTS AT DL CAKE AND BAKERY USING TRANSPORTATION METHODS - Rani,; Eva Zuraida,; Faizal Roni,; Saddam Hussaen, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
Distribution and transportation costs are key components of operational expenses that significantly affect business efficiency and competitiveness, particularly for small and medium enterprises (SMEs) in the food sector. This study aims to analyze and optimize distribution costs at DL Cake and Bakery using a transportation model. The methods employed include the North West Corner (NWC), Least Cost (LC), and Vogel’s Approximation Method (VAM) as initial solutions, as well as the Stepping Stone method for optimality testing. Research data were obtained through interviews and direct observations related to shipping costs, inventory capacity, and demand at distribution branches. The results indicate that the distribution problem at DL Cake and Bakery is a balanced transportation problem, with total supply and demand each amounting to 600 units. The NWC and VAM methods produce a total distribution cost of IDR 18,800,000, while the LC method results in a higher cost of IDR 19,650,000. Optimality testing using the Stepping Stone method shows that all opportunity cost values are positive, indicating that the obtained solution is optimal. Therefore, the minimum distribution cost for DL Cake and Bakery is IDR 18,800,000. The findings of this study are expected to serve as a reference for SMEs in implementing transportation methods to improve distribution cost efficiency.